International law and the future of freedom - Barton, John H.; Stacy, Helen; Greely, Henry T. (Stanford : Stanford University Press, 2014)
This study is an exploration into ways to protect our freedoms in the new global international order. It forges a unique approach to the problem of democracy deficit in the international legal system as a whole - looking at how international law concretely affects actual governance. The book draws from the author's mastery of international trade, technology, and financial law, as well as from a wide array of other legal issues, from espionage law, to international criminal law, to human rights law.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Human rights; Liberty; International organization; International law and human rights; Law; Jurisprudence & general issues; International law